Seismic Response Analysis of Ancient Timber Structures Considering Long-Term Corrosion - Honglou Yang; Gang Peng; Jin Wang; Weikun Li; Junqiang Cui; Erjun Jia (Advances in Civil Engineering)
To evaluate the impact of long-term corrosion on the seismic performance of ancient wooden structures, a simplified analysis model of an intact ancient wooden structure was established using, the OpenSees finite element software, considering column rocking, mortise–tenon joints, Dougong joints, and the role of plate. The accuracy of the model was verified by comparing it with the results of the shaking table test. A residual mechanical performance model of mortise–tenon joints and Dougong joints in ancient wooden structures under long-term corrosion was established. The impact of node performance degradation under long-term corrosion on the seismic response and structural vulnerability was studied. The study indicates, that the nonlinear time-history analysis values of the structure are consistent with the experimental values, with a peak displacement error within 10%, indicating a small error. When the performance degradation rate of the Dougong joints is less than 15.8%, the peak displacement increase rate of the structure is less than 5%. However, when the performance degradation rate of the mortise–tenon joints is 5.7%, the peak displacement increase rate of the structure is greater than 16.32%. Under horizontal seismic action, the main factor affecting the lateral displacement of the structure is the performance of the mortise–tenon joints in the column frame layer. The performance degradation of the mortise–tenon joints has a significant impact on the performance of the structure under minor earthquakes, significantly increasing the probability of slight damage and moderate damage. However, under major earthquakes, the impact on the structural performance is relatively small, with a slight increase in the probability of severe damage and collapse.